2014
DOI: 10.1021/ci500469f
|View full text |Cite
|
Sign up to set email alerts
|

Creating Context for the Experiment Record. User-Defined Metadata: Investigations into Metadata Usage in the LabTrove ELN

Abstract: The drive toward more transparency in research, the growing willingness to make data openly available, and the reuse of data to maximize the return on research investment all increase the importance of being able to find information and make links to the underlying data. The use of metadata in Electronic Laboratory Notebooks (ELNs) to curate experiment data is an essential ingredient for facilitating discovery. The University of Southampton has developed a Web browser-based ELN that enables users to add their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…These issues included refining metadata and improving functionalities in repositories that enabled scholarly use and reuse of materials. Willoughby and colleagues illustrated some of the challenges related to data quality when reporting on researchers in chemistry, biology, and physics [38]. They found that when filling out metadata for a repository, researchers used a ‘minimum required’ approach.…”
Section: Discussionmentioning
confidence: 99%
“…These issues included refining metadata and improving functionalities in repositories that enabled scholarly use and reuse of materials. Willoughby and colleagues illustrated some of the challenges related to data quality when reporting on researchers in chemistry, biology, and physics [38]. They found that when filling out metadata for a repository, researchers used a ‘minimum required’ approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although more research would be needed to identify more effective combination of cues, another approach we have advocated in the past is to make use of ‘invitations’ within interfaces; invitations are prominent interface elements that encourage users to add specific content to an entry [ 28 ]. These invitations could be used instead of ‘mandatory’ fields that potentially confuse or frustrate users.…”
Section: Discussionmentioning
confidence: 99%
“…Our separate study of metadata usage in LabTrove took account of the underlying purpose of each notebook. 13 The majority of the notebooks that we surveyed are used for recording experiments, with other notebooks being used for experiment-related data such as materials catalogues and instrument descriptions. Some groups use the ELN for administrative purposes, such as recording project and personal activities, testing of and discussion about LabTrove itself; a small number of notebooks are used for multiple purposes, comprising both experimental data and project information.…”
Section: Usage Synopsis: How the Eln Has Been Usedmentioning
confidence: 99%
“…We also appraise the reticence shown towards capturing metadata, although we examine the subject of metadata in ELNs at greater depth in a separate article. 13 …”
Section: Introductionmentioning
confidence: 99%